Options for segmenting the mature consumer - Robson, Sarah (Henry Stewart Talks, 2009)
Why is the mature audience important?, Why is the mature market different?, Demographic segmentation, Socio-demographic segmentation, Geo-demographic segmentation, Attitudinal or lifestyle segmentation, Behavioral or transactional segmentation